Pro inflammatory interleukins and thyroid function in Naswar (dipping tobacco) users: a case control study. Issue 1 (December 2016) - Sajid, Faiza; Bano, Samina
Abstract Background Naswar is a type of finely ground, moistened smokeless dipping tobacco product being commonly used in Pakistan. Although, nicotine is the most important psychoactive agent present in Naswar, it also exerts immunosuppressive effects and could alter the levels of cytokines. Additionally, the effects of Naswar consumption on thyroid hormones are not known. Methods Eighty healthy males aged 16–43 years were selected for the study and were divided into a control group comprising 31 healthy subjects with no history of tobacco use in any form, with age matched test group comprising 49 exclusive Naswar users who were consuming Naswar for at least 1 year. Estimation of serum interleukin (IL)-1β, IL-6, free thyroxine (FT4), free triiodothyronine (FT3) and thyroid stimulating hormone (TSH) was carried out. The data was analyzed by statistical programme (SPSS) using student's independent samplest -test. One way Anova followed by post hoc Tukey test was applied to assess parameters in Naswar users grouped according to duration of Naswar usage. Pearson's correlation coefficient was applied to assess correlations between parameters. Results IL-1β was found to be significantly lowered in Naswar users compared to the control group whereas serum FT3 and FT4 levels in Naswar users were significantly raised compared to the control group. However, no differences in the levels of serum IL-6 and TSH between Naswar users and the control group were found. Also, serum FT3 and FT4 were consistently raised whereas IL-1β was lowered in Naswar users irrespective of duration of Naswar consumption. IL-1β was negatively correlated with FT3 in Naswar users. Conclusion The findings suggest that Naswar users might be in an immune suppressive state as evident by the lowered levels of interleukin 1β. Additionally, alterations in the levels of thyroid hormones signify the impact of Naswar consumption on thyroid function.